Topological Properties of Rough Soft Formal Context - Fu, Li (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, the topological structure is discussed in the rough soft formal context. The rough soft formal context is defined on the rough formal context with some soft operators, the topology and the topological space are given in the rough soft formal context. And some topological properties are discussed over the rough soft formal context.